WHAT SHOULD TEACHERS DISCOVER FOR STUDENTS’ SPEAKING NEEDS: REINVENTING A FLIPPED LEARNING FOR UNDERGRADUATE STUDENTS - Anditasari, Amira Wahyu; Aziz, Muhyiddin; Sitompul, Siti Kholija (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This study aimed to discover students' speaking needs to reinvent the flipped-learning model in the teaching speaking context. The needs were carried out through survey design by distributing Google form questionnaires to investigate the students' necessities, lacks, and wants. The questionnaire was a Likert-scale questionnaire consisting of 27 questions. The subject participating in this study was the 53 first-year students of the English study program at one state polytechnic in Madiun. The results of the study were classified into three aspects of speaking; goals, proficiency, and wants, that were integrated with the discussion of the FL model. According to the students, speaking skills were burdensome as good accuracy, fluency, and pronunciation were difficult to achieve. Students essentially used speaking skills as the primary tool to support their national and international careers; thus, students need to be drilled and encouraged to speak English with an appropriate learning approach; one of the relevant approaches was the Flipped Learning (FL) model. Found by scholars that the FL model was believed to emphasize a communicative activity in teaching speaking by prioritizing two different hybrid learning situations; inside and outside class activities. The learning activities in the FL class provide students with autonomous learning, which help them increase their confidence in speaking. Generally speaking, learning activities in the FL model need to be adjusted to the lack, necessities and wants of the students who are involved in the activities. Therefore, the results of the questionnaire will become a reflection and reference to designed learning activities and materials based on the FL model to provide EFL students with appropriate materials that have two functions; grant students with excellent materials and impart self-improvement for students' speaking skills.